Interleukin-33 Contributes to the Induction of Th9 Cells and Antitumor Efficacy by Dectin-1-Activated Dendritic Cells - Chen, Jintong; Zhao, Yinghua; Jiang, Yuxue; Gao, Sujun; Wang, Yiming; Wang, Dongjiao; Wang, Alison; Yi, Huanfa; Gu, Rui; Yi, Qing; Wang, Siqing (Frontiers in Immunology, 2018)
We recently discovered that dectin-1-activated dendritic cells (DCs) drive potent T helper (Th) 9 cell responses and antitumor immunity. However, the underlying mechanisms need to be further defined. The cytokine microenvironment is critical for Th cell differentiation. Here, we show that dectin-1 activation enhances interleukin (IL)-33 expression in DCs. We found that blocking IL-33/ST2 inhibits dectin-1-activated DC-induced Th9 cell differentiation. More importantly, the addition of IL-33 further promotes Th9 cell priming and antitumor efficacy induced by dectin-1-activated DCs. Mechanistically, in addition to the promotion of Th9 and Th1 cells, dectin-1-activated DCs combined with IL-33 abolish the activity of IL-33 in the induction of regulatory T (Treg) cells. Furthermore, the combined treatment of dectin-1-activated DCs and IL-33 increases the frequencies of CD4+ T cells by fostering their proliferation and inhibiting their exhaustive differentiation. Thus, our results demonstrate the important role of IL-33 in dectin-1-activated DC-induced Th9 cell differentiation and antitumor efficacy, and suggest that the combination of dectin-1-activated DCs and IL-33 may present a new effective modality of DC-based vaccines in tumor immunotherapy.